A strong regioregularity effect in self-organizing conjugated polymer films and high-efficiency polythiophene: fullerene solar cells - Kim, Youngkyoo; Cook, Steffan; Tuladhar, Sachetan M.; Choulis, Stelios A.; Nelson, Jenny; Durrant, James R.; Bradley, Donal D.C.; Giles, Mark; McCulloch, Iain; Ha, Chang-Sik; Ree, Moonhor (My University, 2006)
The influence of polymer regioregularity (RR) on the molecular nanostructure, and on the resulting material properties and device performance was analyzed. Annealed blend films show increased α regardless of RR, that indicates improved charge-carrier diffusion. It was found that the highest device efficiencies will be achieved with the highest RR P3HT. It was also found that the dark-current density of as-fabricated devices made with pristine P3HT increases with the RR of P3HT in the higher voltage regime
Keywords: Polymers; Fullerenes; Nanostructured materials; Plastic films; Solar cells